2013
DOI: 10.1177/1049909113479440
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care Attitudes, Values, and Practices Among Health Care Workers

Abstract: To avoid cumbersome through well-meant interventions, it is important that the caregiving team is aware of the patient's own wishes with respect to EOLC issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Several studies [13,[16][17][18] found that it was a combination of the treating oncologist's di culty in transitioning from curative to palliative care and the unrealistic expectations from patients and their families. Also, physicians tend to overestimate the chance of survival [19,20]. In a study by T. S. Chang et al, suggested that treating physician had more aggressive attitude in treating patients at their end of life and gave more intensive management to their patients [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [13,[16][17][18] found that it was a combination of the treating oncologist's di culty in transitioning from curative to palliative care and the unrealistic expectations from patients and their families. Also, physicians tend to overestimate the chance of survival [19,20]. In a study by T. S. Chang et al, suggested that treating physician had more aggressive attitude in treating patients at their end of life and gave more intensive management to their patients [21].…”
Section: Discussionmentioning
confidence: 99%
“…The second concern is that it is often unclear whether the conclusions drawn from studies about autonomy are derived from the experiences of dying people (Monforte-Royo et al, 2011; Ohnsorge et al, 2014a). At times, the conclusions are based on the views of healthcare professionals (Kelner, 1993; Peretti-Watel et al, 2003; Seale, 2009; Goel et al, 2014), or the perspectives of family members or the general public (Chambaere. et al, 2012; Inthorn et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There were circumstances, however, in which hastening the end of a life seemed the only apparent way to relieve suffering. Several countries or states have legislation permitting or decriminalizing euthanasia; these include Belgium, Finland, New Zealand, Netherlands, Norway, Sweden, Switzerland, Thailand and the United States [ 1 - 3 ].…”
Section: Introductionmentioning
confidence: 99%